Strategic observation of internal audit work as part of management support in modern business ways in Republic of Serbia - Veselinović Ana (Megatrend Revija, 2022)
Strategic observation of internal audit in the real business conditions of heterogeneous legal entities in transition economies like the Republic of Serbia enables top management to improve, first of all, the management position in the company. In addition to the above, this approach to internal audit enables top management to make safe business decisions, contributes to the improvement of business decision-making and contributes to making business de-cisions that are economical, efficient and expedient. In general, strategic business decision-ma-king should be viewed as part of the introduction of internal control factors, where internal audit is certainly of great importance. The monitoring of the internal audit should be such that its work can be carried out smoothly in accordance with organizational independence. Such an approach implies that internal audit is organized as an independent function in the companies that have implemented it, as well as that it is organized as an independent function and is not part of any business process, i.e. organizational part of the company, and in its work is directly responsible to the manager who is in charge of internal audit operations. Such an approach is basically a modern approach that has elements of a safe approach, a strategic base that is particularly important for making valid audit findings and recommendations, all of which are made in the sense of increasing the security of making a valid business education of top management. The new or strategic principle of the organization of internal audit represents a unique way of doing business within the overall socio-economic changes that may occur primarily in transitional economies such as Republic of Serbia.